2016
DOI: 10.1155/2016/6126385
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mercury in Dental Silver Amalgam: An Occupational and Environmental Assessment

Abstract: The objective of this study was to assess the occupational exposure to mercury in dentistry and associated environmental emission in wastewater of Lahore, Pakistan. A total of ninety-eight blood samples were collected comprising 37 dentists, 31 dental assistants, and 30 controls. Results demonstrate that the dentistry personnel contained significantly higher mean concentration of mercury in their blood samples (dentists: 29.835 µg/L and dental assistants: 22.798 µg/L) compared to that of the controls (3.2769 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
(46 reference statements)
1
12
0
Order By: Relevance
“…This is because of the administration of dental amalgam, which consists of 50% Hg . Numerous studies have reported that dental personnel have notable higher mean levels of Hg in their blood samples compared to unexposed persons, especially in the older age group of dentists and dental assistants . One study showed that 8% of dentists had higher hair Hg levels than 10 ppm, and 25% had a Hg level above 5 ppm …”
Section: Occupational Exposure To Mercurymentioning
confidence: 99%
“…This is because of the administration of dental amalgam, which consists of 50% Hg . Numerous studies have reported that dental personnel have notable higher mean levels of Hg in their blood samples compared to unexposed persons, especially in the older age group of dentists and dental assistants . One study showed that 8% of dentists had higher hair Hg levels than 10 ppm, and 25% had a Hg level above 5 ppm …”
Section: Occupational Exposure To Mercurymentioning
confidence: 99%
“…Another study revealed that 180 dentists in the West of Scotland had more than four times higher urinary Hg concentrations than non‐occupationally exposed control subjects . In a study from Pakistan, the blood Hg values of 37 dentists and 31 dental assistants were 29.8 µg Hg/L and 22.8 µg Hg/L, respectively, compared with 3.3 µg Hg/L for the controls . It has been shown that dental personnel exposed to elemental Hg have a decreased activity of the selenoenzyme glutathione peroxidase and the metalloenzyme superoxide dismutase in blood, which can be correlated with their duration of dental work .…”
Section: Mercury Exposure and Neuropsychological And Cognitive Symptomentioning
confidence: 99%
“…The SCENIHR review noted one study that found violations of environmental and personal safety standards in 67% and 45% of clinics visited, respectively (Ritchie et al 2004). Some recent studies also revealed violations of occupational safety regulations and indicated the need for more training on the safe use of dental amalgam, properly ventilated dental clinics, and oversight (Jamil et al 2016; Khwaja Mahmood et al 2016). The study by Khwaja Mahmood and colleagues (2016) also highlighted the fact that there is still a high level of dental amalgam use among dentists in Pakistan, even in children and pregnant women, and that use can vary dramatically by location.…”
Section: Position Statement On the Safety Of Dental Amalgammentioning
confidence: 99%